2015
DOI: 10.1103/physrevd.91.095017
|View full text |Cite
|
Sign up to set email alerts
|

Neutron electric dipole moment and probe of PeV scale physics

Abstract: The experimental limit on the neutron electric dipole moment is used as a possible probe of new physics beyond the standard model. Within MSSM we use the current experimental limit on the neutron EDM and possible future improvement as a probe of high scale SUSY. Quantitative analyses show that scalar masses as large as a PeV and larger could be probed in improved experiment far above the scales accessible at future colliders. We also discuss the neutron EDM as a probe of new physics models beyond MSSM. Specifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Besides (g −2) µ , it has been for instance pointed out that VL colored sparticles provide extra contributions to the Higgs boson mass [38][39][40][41][42][43], that VL quarks could possibly explain [44] the recently emerged ttH anomaly [45], and that VL superfields might ameliorate to some extent the fine tuning associated with large stops with respect to the MSSM [46]. On the observational side, it has been shown that signatures of extra VL matter can be tested in the next generation of experiments probing lepton flavor violating decays [47], electric and chromoelectric dipole moments [48,49], flavor violating Higgs decays [50] and rare meson decays.…”
Section: Contentsmentioning
confidence: 99%
“…Besides (g −2) µ , it has been for instance pointed out that VL colored sparticles provide extra contributions to the Higgs boson mass [38][39][40][41][42][43], that VL quarks could possibly explain [44] the recently emerged ttH anomaly [45], and that VL superfields might ameliorate to some extent the fine tuning associated with large stops with respect to the MSSM [46]. On the observational side, it has been shown that signatures of extra VL matter can be tested in the next generation of experiments probing lepton flavor violating decays [47], electric and chromoelectric dipole moments [48,49], flavor violating Higgs decays [50] and rare meson decays.…”
Section: Contentsmentioning
confidence: 99%
“…As a consequence the quark mass matrices are 5 × 5 and the squark mass squared matrices are 10 × 10 and this time we have also the dependence on the vectorlike mass M X . Thus the analysis of this work is more general than of the work of [23]. Gluino Mass, mg (TeV) Other parameters are the same as in Fig.…”
Section: Mirror Up Quarkmentioning
confidence: 99%
“…Again as in the case of CEDM we find that EDM also has a sensitive dependence on M X . We note here that the analysis of this work for EDM is more general than the analysis of [23]. Thus in [23] we considered only the mixings of the three generations with the mirror generation so that the quark matrices were 4 × 4 and the squark square matrices were 8 × 8 and the parameter M X did not appear in that work.…”
Section: Mirror Up Quarkmentioning
confidence: 99%
See 2 more Smart Citations